(3GdYeOI aj Yjhf UMGM GdCNHGQ aj efGbH EeGe GdCHQGQs - (3GdCSOj GdMdj, CHh GdMSjf, GHf GdHWQjb GdMdj, jMji Hf GdMSf Hf GdMSjf GHf GdHWQjb GdMdj, J (B600(3g` (B1204(3es
(3ChdgG (B:s
(3ChdgG(B: (3ef WQjbg KHJ YfO NUeg hEf cGf ZjQ Qajbg KHJ Cfg gh MLI MLI GdeYHhO hTajY GdeUOhO hYUeI GddGLj hEeGe GdefGMjs
(3BNQgG (B:s
(3BNQgG(B: (3hdG jQLY hGbYg Yfg fRGY efGRYI dCf dg hbY Pdc Ydi WQjb GdecGHQI hGdMLGL heMXhQ Ydjg hbY eG hQO aj GdUMGM heG GVafGg EdjgeG dCfgeG CUhd GdGMJLGLs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 141s
(3GdPQjYI, L (B15: 241s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds